PEMBELAJARAN BAHASA BAGI ANAK TUNARUNGU - Murni Winarsih (Perspektif Ilmu Pendidikan, 2010)
Basic thought of this research was begun from communication ability of hearing impairment child at SLB-B X. This communication can be understood by people and the child can get one’s message through speaking. The purpose of this research is to know language learning of hearing impairment child of TLO class at SLB-B X Jakarta with MMR method. This research used qualitative approach with case study as a strategy. Data collections were done by interview, observation and documentation. The data were analyzed by interactive model through data reduction, data display, data conclusion, and data verification. The result of research shows that teachers of TLO SLB-B X have good comprehension of condition and language acquisition of hearing impairment. They also have implemented language learning with MMR principles and have done language stimulation to children through BPBI and Bina Wicara implementation. Language learning at TLO class is supported by school policies .